2021
DOI: 10.3906/sag-2008-5
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory complications of vocal fold injection with hyaluronic acid: a multiinstitutional study

Abstract: Background/aim: This study aimed to assess the inflammatory adverse reactions of vocal fold injection laryngoplasty with hyaluronic acid. Materials and methods: This study was a retrospective chart review of patients who underwent vocal fold injection augmentation with HA injection from January 2005 to September 2016 in nine different institutions. Demographic data, indication for injection, injection techniques, types of injection material, settings of procedure, and complications were reviewed. The types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…None of the patients under study developed adverse effect due to injection in both groups. In contrary, Enver et al, (2021) detected inflammatory complications in 2% of cases injected with hyaluronic acid [19] . Zapanta et al, (2004) reported a case of laryngeal abscess after alloderm injection [20] .…”
Section: Discussionmentioning
confidence: 92%
“…None of the patients under study developed adverse effect due to injection in both groups. In contrary, Enver et al, (2021) detected inflammatory complications in 2% of cases injected with hyaluronic acid [19] . Zapanta et al, (2004) reported a case of laryngeal abscess after alloderm injection [20] .…”
Section: Discussionmentioning
confidence: 92%
“…Seven in total (1.7%) developed inflammatory reactions. 5 Review of the literature also demonstrated an extra-thyroidal neck abscess thought to be secondary to extra laryngeal injection of CaHA into the superficial neck space. 6 One patient experienced anaphylaxis after CaHA injection 2 and another pulmonary embolism due to the foreign body.…”
Section: Discussionmentioning
confidence: 96%
“…29 Complications associated with HA IL can be classified into 2 categories: technical problems, such as hematoma and submucosal injection, and inflammatory reactions caused by ischemic events, hypersensitivity reactions, and acute bacterial infections. 11 An animal study conducted to assess the safety profile of HA/D demonstrated minimal inflammatory reaction on histological examination of rabbit vocal folds 6 months after injection, with no foreign body reactions observed. 30 In one of the largest case series in the literature, Dominguez et al 29 reported an incidence of inflammatory reactions after HA IL of 3.8% (7 out of 186 patients).…”
Section: Discussionmentioning
confidence: 97%
“…Another case series that used HA/D and HA for IL reported side effects in 9 out of 476 patients (1.9%). 11 Of these patients, 2 experienced technical problems, while 7 experienced inflammatory reactions. In the current study, none of the patients experienced any side effects after IL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation